Dose-dependent interaction of dietary vitamin B2 and E in relation to cognitive performance: a cross-sectional study of older adults - Wu, Yueju; Zhou, Hai; Cai, Yong; Du, Wenjuan; Li, Chaonian; Sun, Minli (Frontiers in Nutrition, 2025)
BackgroundWhile individual associations of dietary vitamins with cognitive function have been widely studied, the combined role of vitamin B2 and E remains poorly understood. This study investigates their interactive effects on cognitive performance in older adults.MethodsIn this cross-sectional analysis of 2,497 participants (age ≥60 years) from NHANES 2011–2014, cognitive function was assessed using the Digit Symbol Substitution Test (DSST), with low performance defined as DSST scores <33 (lowest quartile). Dietary intake of vitamins B2 and E was derived from two 24-h recalls. Multivariable logistic regression models adjusted for sociodemographic, lifestyle, and clinical covariates examined independent and joint associations, with interaction effects quantified using product terms.ResultsFollowing comprehensive adjustment, elevated dietary intake of vitamin B2 [odds ratio (OR) = 0.74, 95% confidence interval (CI): 0.58–0.95] and vitamin E (OR = 0.73, 95% CI: 0.56–0.94) was independently associated with diminished odds of low cognitive function. A significant multiplicative interaction was observed (OR = 1.15, 95% CI: 1.05–1.26; p < 0.05). Marginal effect analyses revealed synergistic benefits between vitamins B2 and E at vitamin E intakes <18 mg/day, whereas antagonistic interaction emerged beyond this threshold. Furthermore, stratified analyses identified the strongest protective effects in the high-B2 + low-E group (OR = 0.56, 95% CI: 0.32–0.98) and the dual-high intake group (OR = 0.44, 95% CI: 0.27–0.73) compared to the dual-low intake group.ConclusionOur findings highlight a dose-dependent interplay between vitamins B2 and E in modulating cognitive performance, advocating for dietary guidelines to prioritize nutrient interaction patterns in aging populations.